An Anti‐Cancer Drug Candidate OSI‐027 and its Analog as Inhibitors of mTOR: Computational Insights Into the Inhibitory Mechanisms. Issue 12 (1st June 2017) - Rehan, Mohd
ABSTRACT: The mammalian target of rapamycin (mTOR) is a serine‐threonine kinase, which regulates cellular metabolism and growth, and is a validated therapeutic target in various cancers. Recently, OSI‐027, a selective ATP competitive inhibitor of mTOR, has been developed. The OSI‐027 is an orally bioavailable compound whose anti‐cancer activities were observed in various cancer cell lines and tumor xenograft models. The current study is the first attempt to explore the binding mode and the molecular‐interactions of OSI‐027 with mTOR using molecular docking and (un)binding simulation approaches. The study identified various interacting residues and their extent of involvement in binding was emphasized using different methods. The (un)binding simulation analyses provided snapshots of various phases in OSI‐027 binding and identified residues important for binding but away from the catalytic site. Further, to explore a better binder for mTOR among OSI‐027 analogs, the virtual screening led to propose an OSI‐027 analog with CID: 73294902 as a better inhibitor than the OSI‐027 and the native ligand PI‐103. The binding mode of the proposed compound is compared with those of OSI‐027 and other native inhibitors. The comparison of (un)binding simulation phases of proposed compound with that of OSI‐027 revealed that both, bound to the same catalytic site, follow different (un)binding path. Thus, the current study presents computational insights into the OSI‐027 mediated inhibition of mTOR kinase and proposed an OSI‐027 analog as better mTOR inhibitor, and thus, a good drug for further research in experimental laboratories. J. Cell. Biochem. 118: 4558–4567, 2017. © 2017 Wiley Periodicals, Inc. Abstract : An anticancer drug OSI‐027 is an mTOR inhibitor. The present work explored the binding mode of OSI‐027 with mTOR. Further, in pursuit of better binder, virtual screening of OSI‐027 analogs yielded a compound with PubChem ID, CID: 73294902, which is proposed to be better inhibitor than OSI‐027 and the known native inhibitors including PI‐103.